Biodegradable biliary stents have a different effect than covered metal stents on the expression of proteins associated with tissue healing in benign biliary strictures. (2nd July 2016) - Siiki, Antti; Jesenofsky, Ralf; Löhr, Matthias; Nordback, Isto; Kellomäki, Minna; Gröhn, Heidi; Mikkonen, Joonas; Sand, Juhani; Laukkarinen, Johanna
Abstract: Background: Benign biliary strictures (BBS) are primarily treated endoscopically with covered self-expandable metal stents (CSEMS). Biodegradable biliary stents (BDBS) may be the future of endoscopic therapy of BBS. The aim was to assess the expression of proteins related to tissue healing in BBS compared with the intact bile duct (BD), and to study the protein expression after therapy with CSEMS or BDBS. Methods: Pigs with ischemic BBS were endoscopically treated either with BDBS or CSEMS. Samples were harvested from pigs with intact BD ( n = 5), untreated BBS ( n = 5), and after six months of therapy with BDBS ( n = 4) or CSEMS ( n = 5) with subsequent histologic analysis. Two-dimensional electrophoresis with protein identification was performed to evaluate protein expression patterns. Results: In BBS, the expression of galectin-2 and annexin-A4 decreased, compared to intact BD. Treatment with biodegradable stents normalized galectin-2 level; with CSEMS therapy it remained low. Transgelin expression of intact BD and BBS remained low after BDBS treatment but increased after CSEMS therapy. Histologic analysis did not show unwanted foreign body reaction or hyperplasia in the BD in either group. Conclusions: The expression of proteins related to tissue healing in BBS is different after treatment with biodegradable stents and CSEMS. Treatment with biodegradable stents may bring protein expression towards what is seen in intact BD. BDBS seem to have a good biocompatibility.